2017
DOI: 10.1021/acs.jafc.7b00408
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of Polymethoxyflavones by Human Gut Bacterium, Blautia sp. MRG-PMF1

Abstract: Polymethoxyflavones (PMFs) were biotransformed to various demethylated metabolites in the human intestine by the PMF-metabolizing bacterium, Blautia sp. MRG-PMF1. Because the newly formed metabolites can have different biological activities, the pathways and regioselectivity of PMF bioconversion were investigated. Using an anaerobic in vitro study, 12 PMFs, 5,7-dimethoxyflavone (5,7-DMF), 5-hydroxy-7-methoxyflavone (5-OH-7-MF), 3,5,7-trimethoxyflavone (3,5,7-TMF), 5-hydroxy-3,7-dimethoxyflavone (5-OH-3,7-DMF),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 34 publications
3
57
0
Order By: Relevance
“…Some Fusobacterium members are animal pathogens [63], but their consistent presence in wild bird guts [2,14,64,65], especially in herbivorous species [64][65][66], suggests a possible symbiotic role. Bacteria from the genus Blautia may facilitate the metabolism of plant secondary metabolites [67,68], consistent with an increase in the relative abundance of this genus in birds feeding on seeds. Ruminococcus bacteria (e.g., the R. gauvrauii and R. gnavus groups) that increased signi cantly with seed diet are within the family Lachnospiraceae and their possible functions are poorly resolved [69].…”
Section: P Major Gut Microbiomes Respond To Diet Changes But Not Asmentioning
confidence: 56%
“…Some Fusobacterium members are animal pathogens [63], but their consistent presence in wild bird guts [2,14,64,65], especially in herbivorous species [64][65][66], suggests a possible symbiotic role. Bacteria from the genus Blautia may facilitate the metabolism of plant secondary metabolites [67,68], consistent with an increase in the relative abundance of this genus in birds feeding on seeds. Ruminococcus bacteria (e.g., the R. gauvrauii and R. gnavus groups) that increased signi cantly with seed diet are within the family Lachnospiraceae and their possible functions are poorly resolved [69].…”
Section: P Major Gut Microbiomes Respond To Diet Changes But Not Asmentioning
confidence: 56%
“…An in vitro study showed that Blautia sp. MRG-PMF1 bio-transformed polymethoxyflavones (PMFs) in chrysin, apigenin, galangin, kaempferol, luteolin, and quercetin [60]. This class of flavonoids is involved in many biological functions, among which it exerts important role in anticancer, anti-inflammation, antiallergic, antimutagenicity, and neuroprotection activities.…”
Section: Lachnospiraceae Metabolismmentioning
confidence: 99%
“…In fact, in rat liver microsomes, tangeretin is metabolized to 4'-hydroxy-5,6,7,8-tetramethoxyflavone and 3',4'-dihydroxy-5,6,7,8-tetramethoxyflavone [44]. Even at intestinal levels, the metabolism of PMF leads to the formation of demethylated metabolites by intestinal bacteria [45,46]. After 4 h by oral administration, only 24% of tangeretin was detected in the organs and digestive tract, indicating that approximately 76% of flavone is absorbed or retained in the lumen of the digestive tract as metabolites, such as demethylated derivatives [44].…”
Section: Absorption Uptake and Pharmacokineticsmentioning
confidence: 99%
“…At systemic circulation level, diosmetin is enzymatically esterified to its relevant metabolite, 3-O-glucuronide, which is further esterified into 3,7-di-O-glucuronide [47,48]. Experimental evidence has shown that diosmin has the ability to inhibit P-glycoprotein [45] and several cytochrome P450 (CYP) enzyme isoforms (CYP1A1, CYP1A2, CYP2B1, CYP2C8, CYP2C9, CYP2D6, CYP2E1, CYP3A4, and CYP3A5). Specifically, the inhibition of drug-biotransformation CYP 450 enzymes [49] influences metabolic and pharmacokinetic properties of themselves and other simultaneously administered drugs [50].…”
Section: Absorption Uptake and Pharmacokineticsmentioning
confidence: 99%